ANALISIS ECONOMIC BURDEN OF DISEASE DENGAN METODE COST OF ILLNESS PADA PENDERITA HIPERTENSI DI KOTA SURABAYA TAHUN 2015 - Primayanti . (JURNAL PENELITIAN KESEHATAN, 2016)
Indonesia in recent decades has faced the higher of Non Communicable Diseases (NCDs). Many catastrophic disease begins from NCDs. The main NCDs in Surabaya are  hypertension with aprevalence of 6.10% . If not controlled,  NCDs  would be a burden in terms of health financing.Economic Burden Of Disease (BOD) can be defined as an economic burden caused by a diseaseprocess that affects a person and the family. Estimation of BOD is very important as the scientificevidence for developing public health policy. Metode : This research aim to analyze the economic burden of the patient as a result ofhypertension.  This research use “cost of illness” method. COI method is calculating direct cost andindirect cost that must be borne the patient caused of disease. In order to estimate BOD, the costsis to be calculated with DALY and Prevalence. DALY expressed as the cumulative number of yearslost due to ill health, disability or early death. Prevalence is the proportion of individuals in apopulation having a disease or characteristic. The technique of sampling use “multistage randomsampling” on 48 patients with hypertension, from  Public Health Centres which represents fiveareas of the city of Surabaya. Furthermore, the research result are calculated using the cost ofillness and estimate economic BOD. Results : This analysis shows that the economic burden on hypertension are very high forthe patient. The direct cost of hypertension is IDR 1.348.583,-; The indirect cost of hypertension isIDR 1.056.197,-; Economic Burden Of Disease of ill patients is IDR  4.498.999.294.464,-; EconomicBurden Of Disease of died patients is IDR  76.342.735.689,-  Keywords : Cost of Illness, Government Budget,  Burden of Disease, Hypertension